Medicines associated with dependence or withdrawal: a mixed-methods public health review and national database study in England - Marsden,J; White,M; Annand,F; Burkinshaw,P; Carville,S; Eastwood,B; Kelleher,M; Knight,J; O'Connor,R; Tran,A; Willey,P; Greaves,F; et al. (Lancet Psychiatry, 2019)
BACKGROUND: Antidepressants, opioids for non-cancer pain, gabapentinoids (gabapentin and pregabalin), benzodiazepines, and Z-drugs (zopiclone, zaleplon, and zolpidem) are commonly prescribed medicine classes associated with a risk of dependence or withdrawal. We aimed to review the evidence for these harms and estimate the prevalence of dispensed prescriptions, their geographical distribution, and duration of continuous receipt using all patient-linked prescription data in England. METHODS: This was a mixed-methods public health review, comprising a rapid evidence assessment of articles (Jan 1, 2008, to Oct 3, 2018; with searches of MEDLINE, Embase, and PsycINFO, and the Cochrane and King's Fund libraries), an open call-for-evidence on patient experience and service evaluations, and a retrospective, patient-linked analysis of the National Health Service (NHS) Business Services Authority prescription database (April 1, 2015, to March 30, 2018) for all adults aged 18 years and over. Indirectly (sex and age) standardised rates (ISRs) were computed for all 195 NHS Clinical Commissioning Groups in England, containing 7821 general practices for the geographical analysis. We used publicly available mid-year (June 30) data on the resident adult population and investigated deprivation using the English Indices of Multiple Deprivation (IMD) quintiles (quintile 1 least deprived, quintile 5 most deprived), with each patient assigned to the IMD quintile score of their general practitioner's practice for each year. Statistical modelling (adjusted incident rate ratios [IRRs]) of the number of patients who had a prescription dispensed for each medicine class, and the number of patients in receipt of a prescription for at least 12 months, was done by sex, age group, and IMD quintile. FINDINGS: 77 articles on the five medicine classes were identified from the literature search and call-for-evidence. 17 randomised placebo-controlled trials (6729 participants) reported antidepressant-a